Exploring the perceived academic readiness in mature-aged military students returning to higher education institutions after hiatus: the case of the South African National Defence College - Motloung, Oratile Puseletso (Stellenbosch : Stellenbosch University, 2025)
Thesis (MMil)--Stellenbosch University, 2025.